Measurement the Physiological Properties of Water Pipe Smokers in Shekhan Distract - M. Al-Saiegh, Abdullah.; Sabri Haji, Turki; Saado Ahmed, Jihan; Azzo Aslo, Alaa; Faris Khalaf, Firas (Kurdistan Journal of Applied Research, 2019)
Smoking is one of the old habits used by humans before 400 years ago, where this custom was exclusively used in males with the development of time, tools, ingredients and flavors that used in hookah the women also started smoking, which led to an increase in the prevalence of use in many countries of the world Smoking is one of the reasons that lead to an increase in the percentage incidence of lung cancer, chronic lung disease ,mouth disease ,teeth deformation and gingivitis. The aim of study to determine physiological status before, during and after smoking water pipe. To knowledge awareness of people of harmful smoking water pipe by interview with them and explain the effect and dangerous of water-pipe smoking on their health. Sample had taken from 200 peoples, 100 of them are water pipe smoker, and other 100 from non-smoker. Sample had been taken through blood collection from 100 who are water pipe smoker and 100 who not smoke, and this include the following physiological test: Heart Rate, Blood Pressure, and Respiratory Flow Rate, in addition with laboratory hematological test Hemoglobin. The results showed an increase in the rate of (Blood pressure, Inspiratory Flow Rate, Heart rate, Hemoglobin) and rates higher after smoking as follow for Blood Pressure after smoking systolic was141.9±6.021 and diastolic 91.75 ±4.459 While the inspiratory flow rate reading after smoking 963.5 ±96.624, the heart rate reading after smoking was 83.27 ±7.84 while the hemoglobin the reading was 15.68 ±0.87 as recorded after finishing smoking . Water-pipe smoking has direct effect on Blood Pressure, Heart Rate and Inspiratory Flow Rate and water pipe smoking has have indirect effect on hemoglobin in smokers